2018
DOI: 10.15672/hjms.2018.642
|View full text |Cite
|
Sign up to set email alerts
|

Chebyshev Wavelet Method for Numerical Solutions of Coupled Burgers Equation

Abstract: This paper deals with the numerical solutions of one dimensional time dependent coupled Burgers' equation with suitable initial and boundary conditions by using Chebyshev wavelets in collaboration with a collocation method. The proposed method converts coupled Burgers' equations into system of algebraic equations by aid of the Chebyshev wavelets and their integrals which can be solved easily with a solver. Benchmarking of the proposed method with exact solution and other known methods already exist in the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…where Y m and y m denote the approximate and exact solutions to the unknown functions at m th knot, respectively. The computational outcomes are obtained and compared with those methods already available in literature like the Chebyshev spectral collocation method (CSCM) (Khater et al, 2008), Fourier pseudo-spectral method (FPM) (Rashid and Ismail, 2009), cubic B-spline collocation method (CBSCM) (Mittal and Arora, 2011), differential quadrature method (DQM) (Mittal and Jiwari, 2012), CBS-based differential quadrature method (CBS-DQM) (Mittal and Tripathi, 2014), quintic B-spline collocation method (QBSCM) (Raslan et al, 2017), Fourier expansion basis differential quadrature method (FEB-DQM) (Jima et al, 2018), Chebyshev wavelets method (CVM) (Oruç et al, 2019) and septic B-spline collocation method (SpBSM) (Shallal et al, 2019).…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…where Y m and y m denote the approximate and exact solutions to the unknown functions at m th knot, respectively. The computational outcomes are obtained and compared with those methods already available in literature like the Chebyshev spectral collocation method (CSCM) (Khater et al, 2008), Fourier pseudo-spectral method (FPM) (Rashid and Ismail, 2009), cubic B-spline collocation method (CBSCM) (Mittal and Arora, 2011), differential quadrature method (DQM) (Mittal and Jiwari, 2012), CBS-based differential quadrature method (CBS-DQM) (Mittal and Tripathi, 2014), quintic B-spline collocation method (QBSCM) (Raslan et al, 2017), Fourier expansion basis differential quadrature method (FEB-DQM) (Jima et al, 2018), Chebyshev wavelets method (CVM) (Oruç et al, 2019) and septic B-spline collocation method (SpBSM) (Shallal et al, 2019).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The error norms L 1 and L 2 for Example 3, corresponding to different choices of spatial grid size at t = 1, by setting Dt = 0.01 and l = 0.1,0.4, are listed in Table 7. In Tables 8 and 9, a comparison of computational outcomes with CVM (Oruç et al, 2019) is presented for different values of M at t = 3 and 5 using fixed Dt and l . It is revealed that our commuted results exhibit a better agreement with the analytical exact solution as compared to CVM.…”
Section: New Cubic Bspline Approximation Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Oruc et al [25,26] applied a unified finite difference Chebyshev wavelet approach for time fractional Burger equations. The same authors studied the Chebyshev wavelet method for approximation of coupled Burgers equations [27]. Ali et al [4] applied a meshfree collocation method based on the Crank-Nicolson method for time discretization and radial basis function for space discretization to solve two-dimensional coupled Burger equations, whereas the meshless method of radial basis functions (RBFs) and local RBFs were described in [28,29] for approximate solutions of Burger-type equations.…”
Section: Introductionmentioning
confidence: 99%
“…A.K. Gupta and S.S. Ray studied the solution of fractional fifth-order Sawada-Kotera equation using second kind Chebyshev wavelet method [14] and many others [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%